2013
DOI: 10.1097/01.aids.0000431945.72365.01
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of HIV-control since seroconversion

Abstract: In most individuals, control occurred rapidly after seroconversion; however, more than 3 years were required to achieve control in 25% of HIV-controllers. Control may be sustained even when CD4⁺ cell levels are below 500 cells/μl, opening important new perspectives to understand the physiopathology underlying control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 24 publications
3
46
1
1
Order By: Relevance
“…Interestingly, CD4 counts also decreased in those who maintained virological control at the end of follow-up, around 9 cells/year, albeit at a slower pace than during natural history [32]. The association between CD4 decline and occurrence of blips during HIV control has been previously described [9,10,12], but here, and for the first time to our knowledge, we were able to model lymphocyte count dynamics before and after viral rebounds. We showed that CD4 counts and CD4/CD8 ratio declined several years before the first viral rebound was clinically observed.…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, CD4 counts also decreased in those who maintained virological control at the end of follow-up, around 9 cells/year, albeit at a slower pace than during natural history [32]. The association between CD4 decline and occurrence of blips during HIV control has been previously described [9,10,12], but here, and for the first time to our knowledge, we were able to model lymphocyte count dynamics before and after viral rebounds. We showed that CD4 counts and CD4/CD8 ratio declined several years before the first viral rebound was clinically observed.…”
Section: Discussionmentioning
confidence: 67%
“…There are many reasons pre-ART individuals may present as aviraemic. A detailed discussion of this phenomenon is beyond the scope of this article, but undisclosed ART use dispensed from a different facility and transient virological control are just two common causes that may confound the use of VL as a confirmatory tool [1920]. In these aviraemic individuals, further serological testing is required, but our calculation suggests that this tandem VL-ELISA approach is 10 times more costly than simply confirming every positive RDT with ELISA alone.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of viral load dynamics early in infection have focused on small numbers of well-characterized elite or viremic HIV controllers, 3-6,16 and most reports from longitudinal cohort studies do not provide detailed information about viremia early in infection. Some studies have suggested that certain HLA alleles (e.g., HLA-B57) have a protective effect that may contribute to lower viral load set points in HIV controllers.…”
Section: Discussionmentioning
confidence: 99%
“…2-4 Other studies have shown that virologic suppression among HIV controllers is usually established within the first year of HIV infection. 3,5,6 In a recent study, over half of the individuals identified as HIV controllers had undetectable viral loads at seroconversion, and 25% achieved viremic control within six months. 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation